The impact of non-stereotypical gender role endorsement in live broadcasting on consumers’ purchase intention - Fu, Jia; Huang, Simin; Chen, Xiaolin (Frontiers in Psychology, 2024)
With the rise of live-stream sales, non-stereotypical gender role endorsement is becoming more common in e-commerce live broadcasting. However, there is relatively little research on this topic, and the mechanism of its impact on purchase intention is not yet clear. Based on schema theory and experimental methods, this study explores the impact of non-stereotypical gender role endorsement (compared to stereotypical gender role endorsement) on purchase intention in e-commerce live broadcasting. Besides, we take traditional gender ideology as the moderating variable. This study conducted experiments on male/female product groups respectively. Experiment 1 indicates that for female product, stereotypical gender role endorsement triggers higher consumer purchase intention compared to non-stereotypical gender role endorsement, which is consistent with the conjecture given by schema congruence theory. The subsequent moderating effect test results manifest that traditional gender ideology plays a moderating role in this effect. Experiment 2 shows that for male product, there is no significant difference in the impact of the two types of endorsement on consumer purchase intention. This study not only has certain theoretical significance for expanding the application boundaries of schema theory and congruence between celebrities and products endorsed, but also has practical significance for brand owners and streamers to effectively adopt nonstereotypical gender role endorsement to enhance purchase intention.